基于径向分流和浮动凹模耦合法圆柱直齿轮冷锻成形数值模拟研究 - 龚冬梅 (Jixie chuandong)
The cold forging forming of spur gear with big modulus is numerical simulated by the method coupled radial divided-flow with floating-die.Then,the metal flow rule and deformation mechanism are got in the deformation course.The simulation results show that the completed gear is formed and the forming force can be greatly reduced by the method.The result provide feasible basis for practice use.